2023
DOI: 10.3390/admsci13030067
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Risk-Taking Behaviour during COVID-19 Pandemic: Will Work–Family Enrichment and Work Satisfaction Prevent Turnover Intention?

Abstract: The COVID-19 pandemic has impacted all employment conditions as working during the pandemic is a risk to employees’ health. This study investigates women’s intentions to leave their job during times of crisis. However, opportunities for job selection were quite limited, and there are better ways to deal with job insecurity than leaving an organisation. The questionnaires were tested on valid data from 593 female employees of four-star hotels, and structural equation modelling (SEM) was employed. Cultural chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Van Dierendonck et al (2016) similarly concluded that dissatisfied employees will look for new opportunities and if they find a better alternative, they will leave their current job. Consistent with the ideas of (Dewi et al 2023), the turnover process begins with employee dissatisfaction, the thought of quitting, job search, and assessment of prospects, and culminates in the decision to quit. The intention to quit is associated with a deterioration in work ethic, more frequent absenteeism, lower levels of productivity, and reduced customer satisfaction.…”
Section: Turnover Intentionmentioning
confidence: 94%
“…Van Dierendonck et al (2016) similarly concluded that dissatisfied employees will look for new opportunities and if they find a better alternative, they will leave their current job. Consistent with the ideas of (Dewi et al 2023), the turnover process begins with employee dissatisfaction, the thought of quitting, job search, and assessment of prospects, and culminates in the decision to quit. The intention to quit is associated with a deterioration in work ethic, more frequent absenteeism, lower levels of productivity, and reduced customer satisfaction.…”
Section: Turnover Intentionmentioning
confidence: 94%
“…Job satisfaction is a person's feelings towards his work which are produced by his efforts (internal) and supported by things outside himself (external), regarding work conditions, work results, and work itself [10] [29]. An employee's positive attitude towards their work arises based on an assessment of the work situation, and this assessment can be carried out on one of their jobs and as a sense of appreciation for achieving one of the important values in work.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…First, Indonesia is a rapidly developing country with a growing workforce and a burgeoning economy. Understanding the factors influencing organizational commitment among Indonesian employees can help organizations enhance employee engagement, reduce turnover, and improve organizational performance (Dewi et al, 2023). Second, Indonesia is a culturally diverse society with a rich history and traditions.…”
Section: Introductionmentioning
confidence: 99%